2008
DOI: 10.1002/pbc.21689
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status at diagnosis of children with malignancies in Casablanca

Abstract: Introduction Nutritional assessment is an essential component of the initial assessment of children with cancer. Malnutrition may be present at diagnosis due to the effects of the malignancy or, in low income countries (LIC), due to poverty and an inadequate diet. Purpose The aim of this study is to evaluate the prevalence of malnutrition at diagnosis in children with cancer in Morocco. Procedure Nutritional status of 100 children aged less than 18 years with newly diagnosed malignancy between January 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
(24 reference statements)
5
31
0
10
Order By: Relevance
“…The observed differences in nutritional status associated with cancer type were consistent with literature that demonstrates that malnutrition at diagnosis is most frequent among patients with solid tumors, especially Wilms tumor or neuroblastoma, and those with AML or myelodysplastic syndrome, and least frequent in ALL and Hodgkin lymphoma, though not reaching statistical significance most likely due to small sample size. Prevalence of malnutrition in patients with newly diagnosed BL was similar to that in patients with AML and should also be considered among the most at risk groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The observed differences in nutritional status associated with cancer type were consistent with literature that demonstrates that malnutrition at diagnosis is most frequent among patients with solid tumors, especially Wilms tumor or neuroblastoma, and those with AML or myelodysplastic syndrome, and least frequent in ALL and Hodgkin lymphoma, though not reaching statistical significance most likely due to small sample size. Prevalence of malnutrition in patients with newly diagnosed BL was similar to that in patients with AML and should also be considered among the most at risk groups.…”
Section: Discussionsupporting
confidence: 89%
“…Cancer confers an additional risk of malnutrition due to increased metabolic rate, anorexia, inflammation, and altered physical activity . Studies in Central America, Morocco, and Malawi have demonstrated high rates of malnutrition (20–59%) in children at the time of cancer diagnosis . Moreover, malnutrition varies widely by disease type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the Malawian patients in a previous study were severely, acutely malnourished [4,5]. Malnutrition reduces immunity to infections and in patients with Burkitt lymphoma is associated with more severe chemotherapy-related toxicity, especially neutropenia [6][7][8].…”
Section: Introductionmentioning
confidence: 95%
“…Penelitian Tazi dkk, 15 mengenai status nutrisi pada saat anak terdiagnosis penyakit keganasan di Casablanca, melaporkan 33% anak dengan malnutrisi. Malnutrisi pada pasien dengan kanker dapat berkaitan dengan beberapa faktor, yaitu keganasan itu sendiri, terapi, kondisi sosial ekonomi, intake makanan, energy expanditure, absorbsi nutrien dan metabolisme dan berbagai komplikasi mengenai mukosa oral, maupun saluran cerna yang dapat berpengaruh terhadap status nutrisi pada anak dengan keganasan.…”
Section: Pembahasanunclassified